Pharmaceutical Approval Update - Choy, Mary (P T, 2016)
Defibrotide sodium (Defitelio) for hepatic veno-occlusive disease; emtricitabine/tenofovir alafenamide (Descovy) for human immunodeficiency virus infection; and infliximabdyyb (Inflectra) for Crohn’s disease, ulcerative colitis, rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, and plaque psoriasis